Enhanced solar-driven water splitting of 1D core-shell Si/TiO2/ZnO nanopillars. (9th October 2020) - Pavlenko, Mykola; Siuzdak, Katarzyna; Coy, Emerson; Załęski, Karol; Jancelewicz, Mariusz; Iatsunskyi, Igor
Abstract: In this work, 1D core-shell Si/metal oxide nanopillar (NP) photoanodes were synthesized for enhanced solar-driven water splitting processes. The core-shell structures were fabricated by atomic layer deposition of different metal oxides (TiO2 and ZnO) onto Si NP, which were synthesized by metal-assisted chemical etching and nanosphere lithography. In order to characterize produced photoanodes various experimental techniques (SEM/TEM, XRD, Transmittance, Reflectance, Raman spectroscopy) were applied. Photoelectrochemical (PEC) water oxidation of produced photoanodes was studied. It was shown that composition of n-Si/TiO2 /ZnO NP exhibited enhanced photocurrents due to barrier effects. The enhanced PEC properties of core-shell Si/TiO2 /ZnO NP are caused by efficient charge separation of photogenerated electron-hole pairs in the TiO2 /ZnO shell and effective holes transfer to the shell-electrolyte interface. The superior photoelectrochemical performance of a photoanode based on core-shell Si/TiO2 /ZnO NP has been confirmed through electrochemical impedance spectroscopy and voltamperometric measurements under electrode irradiation. 1D core-shell Si/TiO2 /ZnO NP offer a new approach for preparing stable and highly efficient photoanodes for PEC water-splitting process. Highlights: 1D core-shell Si/TiO2 /ZnO nanopillars for PEC performance have been produced. Si/TiO2 /ZnO photoanodes exhibit enhanced photoactivity for water splitting. The influence of Si–TiO2 –ZnO interfaces onto the PEC efficiency was shown. The mechanisms of PEC water splitting processes in Si/TiO2 /ZnO were proposed.